[1991 Proceedings] the Twenty-Third Southeastern Symposium on System Theory
DOI: 10.1109/ssst.1991.138507
|View full text |Cite
|
Sign up to set email alerts
|

Modelling, simulation and analysis of variable speed constant frequency wind energy conversion scheme using self excited induction generator

Abstract: Canada SELF EYCIIED POUER -INDUCIION e COHUERSIOH PRlnE IIOUER CEHLRIIOR L I N KAIlSTRACT: This paper presents the dynamic modelling of variable speed constant frequency [VSCF] wind energy conversion scheme [WECS], employing self excited induction generator, connected to the utility grid through an AC-DC-AC converter scheme with Uncontrolled rectilier and PWM inverter. The proposed scheme for regulating the flow of power through the link ensures reduced reactive power burden on the self excitation capacitor ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It can modify the blade's pitch through variable propeller pitch mounting inside the hub, thus change the size of wind energy absorbed [1][2][3].Therefore, the research on the turbine model is not only related to the load of wind turbine and structure design [4],but also has significant sense of complete machine design [5], power quality and wind power output prediction [6].…”
Section: Introductionmentioning
confidence: 99%
“…It can modify the blade's pitch through variable propeller pitch mounting inside the hub, thus change the size of wind energy absorbed [1][2][3].Therefore, the research on the turbine model is not only related to the load of wind turbine and structure design [4],but also has significant sense of complete machine design [5], power quality and wind power output prediction [6].…”
Section: Introductionmentioning
confidence: 99%
“…IND energy conversionhnterface scheme (WECS) using a wind turbine driven self-excited induction generator and line commutatedPWM inverter have been modeled, analyzed, and implemented [ 11- [4]. In remote locations where the utility grid does not exist, stand alone wind energy conversion scheme (SAWESCS) can be used to feed the local electrical load.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the variable magnitude, variable frequency voltage at the self-excited induction generator terminal is first rectified and the dc power is then transferred to the local load through a PWM inverter. It has been shown that the power available from a WES can be approximated as a cubic function of the wind veloci1,y [4], [ 5 ] . To ensure complete utilization of available wind energy under varying wind velocities, most of the schemes reported use a PID controller to track and extract maximum energy.…”
Section: Introductionmentioning
confidence: 99%